The Effect of Slice Service Training on The Accuracy of Tennis Service Hit - Muhammad Rizal Muzaqir; Yadi Sunaryadi; Mochamad Yamin Saputra (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2025)
This study aims to evaluate the effect of slice service training on the accuracy of tennis service strokes. Slice service is a technique that produces a lateral spin, creating a curved ball trajectory that is difficult to anticipate and return, especially for intermediate players. Despite its tactical advantages, this technique is rarely given specific attention in tennis training programs. This research employed a quasi-experimental design with a one-group pretest–posttest approach involving 16 athletes from Caringin Tennis Club aged 18–23 years. The instrument used was the validated Hewitt's Tennis Achievement Test. The results showed a significant increase in service accuracy, with the mean score rising from 17.88 (pretest) to 44.00 (posttest). Paired sample t-test analysis confirmed a statistically significant improvement (p = 0.000). The data met the assumption of normality based on the Shapiro-Wilk test. These findings indicate that structured slice service training effectively improves stroke precision, motor coordination, and confidence during service execution. The study supports the importance of integrating specific technique-based training in tennis coaching, especially during the skill development phase.